2021
DOI: 10.7557/14.4975
|View full text |Cite
|
Sign up to set email alerts
|

Sykepleiere i hjemmebaserte tjenester – hvorfor fortsetter de i sin stilling?

Abstract: Sykepleiere som arbeider i helsetjenester i hjemmet har krav om høy kvalitet på sykepleieutøvelsen. Samtidig har Norge en sykepleiermangel og primærhelsetjenesten utfordringer med å rekruttere og beholde sykepleiere. Studien beskriver og fortolker hva som var viktig for å fortsette i sin stilling som sykepleier i helsetjenester i hjemmet. En kvalitativ design ble benyttet. Deltakerne var seks sykepleiere i alderen 26 til 60 år ansatt i helsetjenester i hjemmet i en distriktskommune. Data ble samlet inn gjennom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In line with previous research [ 6 , 87 ], our findings demonstrate the importance of home care services continuously working to ensure improved collaboration with other health care providers in order to reduce uncertainty and extra work for registered nurses. A sense of accomplishment has been identified as important for nurses’ intention to remain in home care services [ 28 ], and our results indicate that this guides additional career choices. In line with the principle of conservation of resources [ 38 ], acquiring resources makes nurses more employable and provides them with career opportunities inside and outside primary health care.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In line with previous research [ 6 , 87 ], our findings demonstrate the importance of home care services continuously working to ensure improved collaboration with other health care providers in order to reduce uncertainty and extra work for registered nurses. A sense of accomplishment has been identified as important for nurses’ intention to remain in home care services [ 28 ], and our results indicate that this guides additional career choices. In line with the principle of conservation of resources [ 38 ], acquiring resources makes nurses more employable and provides them with career opportunities inside and outside primary health care.…”
Section: Discussionmentioning
confidence: 56%
“…The shortage of registered nurses means that they can choose between many career options. Researchers have investigated the most and least satisfying aspects of work in primary health care [ 25 ], nurses’ job satisfaction and quality of life [ 26 , 27 ], and why home care nurses remain in their jobs [ 28 , 29 ]. Results of these studies identified autonomy, work-life balance, interaction with patients, role diversity, and patient-family interaction as satisfying aspects of work in primary health care and influence nurses’ intention to remain.…”
Section: Introductionmentioning
confidence: 99%